Knowledge, attitudes and beliefs related to drugs among Pahang Matriculation students in Malaysia - Al-Zurfi, Balsam Mahdi Nasir; Fuad, Maher D. Fuad; Ghazi, Hasanain Faisal; AbdalQader, Mohammed A.; Elnajeh, Maged; Baobaid, Mohammed Faez (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2016)
Introduction Drug abuse has been a global threat not only in Malaysia but worldwide, especially among adolescents. This is alarming issue had been a serious public health problem worldwide. The aim of the study is to access the knowledge and attitude on drug abuse among Pahang Matriculation students in 2016. Methods A cross¬-sectional study was conducted involving 217 matriculation students. A self-determined questionnaire was distributed among the students regarding knowledge and attitude about drugs. Results The prevalence of good knowledge on drug abuse was (82.03%). The prevalence of students’ attitude on drug abuse has higher number of good attitude with the sum of 182 (83.9 %). Only gender showed a significant association with students’ knowledge (P= 0.046). Conclusion The knowledge, attitude, and practice of drug abuse among Pahang Matriculation students are good.